MOTIVATION FOR IMPLEMENTING GOOD GOVERNANCE AND THE PUBLIC SATISFACTION INDEX IN THE IMPLEMENTATION OF REGIONAL AUTONOMY IN NENAS SIAM VILLAGE, BATU BARA REGENCY - Muhammad Syafii; Budiman Purba; Tomi Jaffisa (Universitas Dharmawangsa Medan, 2026)
This study analyses the influence of motivation in implementing good governance principles on the Community Satisfaction Index (CSI/IKM) in the implementation of regional autonomy at Nenas Siam Village, Batu Bara Regency. Good governance is conceptualised as a paradigm of public administration grounded in transparency, accountability, responsiveness, effectiveness, efficiency, the rule of law, and public participation. At the village level, the realisation of these principles depends substantially on the motivation of village officials in translating them into daily public service practices. The study uses a quantitative approach with a descriptive-correlational design. Data were collected via a Likert-scale questionnaire administered to 91 respondents drawn from village service users using stratified random sampling. Data analysis included descriptive statistics, validity and reliability tests, classical assumption tests, Pearson correlation, and simple linear regression. The findings show a positive and statistically significant relationship between the motivation to implement good governance and the Community Satisfaction Index. The correlation coefficient falls within the strong category, and the regression results indicate that an increase in officials' motivation contributes meaningfully to higher community satisfaction with public services. The coefficient of determination shows that more than half of the variation in satisfaction can be explained by the motivation to implement good governance. The study concludes that strengthening officials' work motivation through accountable leadership, professional work culture, and CSI-based evaluation mechanisms is a key strategy for improving the quality of regional autonomy at the village level. Keywords: Village Officials' Motivation; Good Governance; Community Satisfaction Index; Public Service; Regional Autonomy